2012
DOI: 10.12816/0003741
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Employee Commitment on Employee Satisfaction Role of Employee Performance as a Moderating Variable

Abstract: Role of employee commitment is always been accepted as an active catalyst for improving organizational satisfaction. In this research employee satisfaction is taken as dependent variable and employee commitment is employed as independent variable, whereas employee performance is used as moderating variable. Sample for this study is selected from employees working in various private and public organizations of major cities of Lahore, Faisalabad and Karachi. Data is collected through close-ended questionnaire an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
0
3
1
Order By: Relevance
“…The results also exhibits some dissimilarities compare with previous findings such as (Khan, Rehman & Akram, 2012), (Rotenberry & Moberg, 2007), (Tennant & Langford, 2006) who explained career development is significant variable for performance. Unlike those findings, this result indicates career development is weak variable.…”
Section: Major Findingscontrasting
confidence: 81%
“…The results also exhibits some dissimilarities compare with previous findings such as (Khan, Rehman & Akram, 2012), (Rotenberry & Moberg, 2007), (Tennant & Langford, 2006) who explained career development is significant variable for performance. Unlike those findings, this result indicates career development is weak variable.…”
Section: Major Findingscontrasting
confidence: 81%
“…Organisational commitment has become a global construct which indicates employees' action in accordance to the objectives of firm (Az, 2017;Boehman, 2006). As indicated by Khan, Zia-ur-Rehman,and Akram, (2012), high state of organisational commitment is helpful to the organization as it enhances employee performance, and reduces employee turnover. Organisational commitment shows the diminishing in the lateness, absenteeism and lackadaisical attitudes of the employees (Az, 2017;Irefin & Mechanic, 2014Hunjira, 2010Lo, Ramayah & Min, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Job involvement as predictor of employee commitment evidence in the context of Pakistan showed that job involvement has been one of the most effective tools used for increasing employee productivity by enhancing employee participation and commitment (Khan, Jam, Akbar, Khan and Hijazi, 2011). Impact of employee commitment on employee satisfaction role of employee performance as a moderating variable showed that role of employee commitment has always been accepted as an active catalyst for improving organizational satisfaction (Khan, Rehman and Akram, 2012). Every organization should develop strategies that strengthen the work environment and increase the employee morale and employee satisfaction to enhance employee performance and productivity, which ultimately results in high profits, customer satisfaction as well as customer retention (Sageer, Rafat and Agarwal, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%